INTRODUCTION OF INNOVATIVE TECHNOLOGIES IN ATHLETICS IN THE CURRICULUM OF HIGHER EDUCATIONAL INSTITUTIONS - Erkin Allomov Ibragimovich (American Journals Publishing, 2023)
This article is about the correction of methods of preparing students Involved in athletics and, in particular, long-distance raise.
Keywords: Strength training, experiment, cardiovascular system, musculoskeletal system.